Izzivi pri prepoznavanju in podpori dvojno izjemnih učencev v izobraževalnem procesu - Hrenič, Sandra (Revija za elementarno izobraževanje, 2025)
Twice-exceptional students, who have giftedness combined with special educational needs, are often overlooked, which hinders the provision of appropriate support in the educational process. This paper analyses the attitudes and competences of professionals working with this group of students, as well as the ways knowledge is acquired in this field. The research results show that most professionals recognize the importance of identifying twice-exceptionality, yet only a few systematically incorporate appropriate pedagogical approaches into practice. Knowledge in this area is mostly gained through informal sources and experience sharing, since formal professional training is limited. The need for developing specialized training programs is emphasized to improve the identification and effective support of this specific group of students.
Keywords: dual exceptional students; dvojno izjemni učenci; giftedness; nadarjenost; posebne potrebe; prepoznavanje; recognition; special needs; teacher training; usposobljenost